PERAWATAN DENTAL FLUOROSIS PADA ANAK - Amandia Dewi Permana Shita (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Dental fluorosis is a health condition caused by a child receiving too much fluoride during tooth development. Excessive fluoride can cause white spots, and in severe cases, brown stains or pitting or mottling of enamel. Dental fluorosis can be cosmetically treated by a dentist. The cost and success can vary significantly depending on the treatment. Tooth bleaching, microabrasion, and conservative composite restorations or porcelain veneers are commonly used treatments. Generally speaking, bleaching and microabrasion are used for superficial staining, whereas the conservative restorations are used for more unaesthetic situations.